ANALYSIS OF THE CYCLONE WIND HAZARD LEVEL BASED ON REMOTE SENSING AND GIS IN PONTIANAK CITY - Agus Sudiro; Rosanti Rosanti; Ajun Purwanto (Universitas Sebelas Maret (UNS), 2025)
Over the past century, numerous cyclones have affected several countries, resulting in significant economic losses. This study uses GIS to determine the Danger Level of Tornadoes and the distribution of areas affected by tornadoes in Pontianak City in 2024. The method used is secondary data analysis. The data analysis technique used is a weighted, tiered quantitative analysis employing the Analytical Hierarchy Process (AHP) approach and the Overlay function in ArcGIS 10.8, utilising the Weighted Overlay spatial analysis tool. The data were rainfall, ground surface temperature, slope, and land cover. The four parameters were made into a map, each weighted using the AHP method. The results showed that the level of danger of tornadoes in Pontianak City in 2024, using GIS and Remote Sensing, has four classes: very low, low, medium, and high. Very low class has an area of 223.86 ha (2%), low class 3510.52 ha (35%), medium class 6262.04 ha (62%) and high class (151.71 ha (1%). Most of the classes of tornado hazard levels are medium. The distribution of this class is mostly in West Pontianak, Pontianak Kota, and South Pontianak sub-districts. The lower class is mostly located in Southeast and North Pontianak.